Vegetation ecology of Central Europe. coastal to alpine, natural to man-made habitats /: coastal to alpine, natural to man-made habitats. Ecology of Central European non-forest vegetation : Volume II, (2017) - Leuschner, Christoph; Ellenberg, Heinz, 1913-
No abstract available